Allah’s wisdom in creating the universe as a source of inspiration in artificial intelligence - Mahmod Attar Bashi, Zainab Senan; Maspo, Nur-Adib; Hassan Abdalla Hashim, Aisha; Senan, Shayma (Centre for Islamisation (CENTRIS), IIUM and Kulliyyah of Information and Communication Technology (KICT), 2024)
In the Quran, the intricate design and harmony of the natural world are presented as signs (ayat) of Allah's existence and attributes, encouraging deep reflection on His creation. This perspective aligns with the importance of Tafakur in Islam, which involves reflecting on the signs of Allah in the universe and understanding His wisdom. As artificial intelligence (AI) continues to transform human capabilities, enabling machines to replicate cognitive functions and behaviours, the importance of balancing material pursuits with spiritual and ethical considerations becomes increasingly significant. AI has revolutionised industries by enhancing efficiency and personalisation, but has also contributed to materialistic influences and consumerism. Islam emphasises the need to balance these pursuits with spiritual and ethical values, highlighting the central role of the Soul (الروح) in human interactions, together with technological advancements. Tafakur is encouraged as a means of strengthening faith and achieving wisdom (حِكمة, hikmah), which involves applying knowledge in a just and purposeful manner. The article further explores how nature-inspired algorithms, such as Particle Swarm Optimisation, Ant Colony Optimisation, and the Bat Algorithm, draw from natural processes to solve complex modern problems, reflecting the Quranic encouragement to seek insights from the natural world. This tradition of learning from nature not only advances knowledge and technology but also aligns with the Islamic view of humanity's role as Khalifah on Earth, integrating spiritual and scientific exploration.